Individuals' career perceptions in different institutionalized contexts: a comparative study of career actors in liberal, coordinated, hierarchical and mediterranean market economies - Andresen, Maike; Apospori, Eleni; Gunz, Hugh; Cotton, Richard; Hall, Douglas T.; Shen, Yan; Bosak, Janine; Dickmann, Michael; Parry, Emma (Wiley, 2023)
Leveraging Weiner's attribution theory of intrapersonal motivation at the micro level and varieties of capitalism theory at the macro level, we conduct a multi-country and cross-level study examining whether individuals' career goals (i.e., perceived importance of learning and development), behaviors (i.e., proactive career behaviors), and outcomes (i.e., perceived employability) as well as the relationships between these variables, differ between different market economies. We challenge extant literature that focuses on the agentic role of individuals and understates the role of context (i.e., market economy influence) in an individual's career development. Using multilevel structural equation modeling, we draw on a survey of 15,201 individuals between 2014 and 2016 from 22 countries representing four different varieties of capitalism. The results showed that workers in hierarchical (HME) and Mediterranean (MME) market economies systematically differed from individuals in coordinated (CME) and liberal (LME) market economies in proactive career behaviors and perceived employability. Moreover, while the positive relationship between perceived importance of learning and development and proactive career behaviors was stronger in CMEs and LMEs compared to HMEs and MMEs, the positive association between proactive career behaviors and perceived employability was weaker. Our study bridges the micro-macro gap in career studies, adding new insights into the ongoing conversation of contextual influence in individuals' career development.
Keywords: attribution theory of intrapersonal motivation; career; market economy; perceived employability; perceived importance of learning and development; proactive career behaviors; varieties of capitalism theory